Social and scientific disorder as epistemic phenomena, or The consequences of government dietary guidelines - Scott Scheall; William N. Butos; Thomas J. McQuade (Duke University, Center for the History of Political Economy (CHOPE), 2018)
We begin with an economic model of science according to which signals concerning scientific reputation both serve to coordinate the plans of individuals in the scientific domain and ensure that the knowledge that emerges from interactions between scientists and the environment is reliable (McQuade and Butos 2003). Under normal circumstances, scientific order emerges from the publication-citation-reputation (PCR) processes of science (Butos and McQuade 2012). We adopt and extend F.A. Hayek's "non-standard" epistemology according to which knowledge affords successful plan-based action (Scheall 2016). We develop an epistemic theory of social order (Scheall 2015). We discuss the distorting effects on scientific knowledge and, thus, on scientific and social order more broadly, of government interference with the PCR processes of science. Finally, we use the history of the United States federal government's development of standardized dietary guidelines for American consumers and its concomitant interference in the PCR processes of nutritional science as an illustration of our synthesized theory of social order. We conclude that this interference contributed to social disorder in dietary science and beyond.
Keywords: B31; D02; D72; H11; H51; I18; 330; social order; scientific order; F.A. Hayek; pretence of knowledge; discovery procedure; epistemic theory; dietary guidelines; fat hypothesis; carbohydrate hypothesis; Gary Taubes